Internationally Validated Open Access Indicators of Large Public Urban Green Space for Healthy and Sustainable Cities - Turner, R; Higgs, C; Heikinheimo, V; Hunter, R; Vargas, JCB; Liu, S; Resendiz, E; Boeing, G; Adlakha, D; Schifanella, R; Rosa, GL; Pugacheva, D; et al. (Wiley, 2025)
Large public urban green spaces (LPUGS) provide multiple health and environmental co-benefits by mitigating urban heat, improving air quality and biodiversity, and promoting physical activity, social interactions, and mental wellbeing. There is a lack of accessible, evidence-informed, and internationally validated LPUGS indicators to assist with benchmarking and monitoring progress toward healthy and sustainable cities globally. This study developed and validated internationally applicable spatial indicators of LPUGS availability and accessibility that are directly relevant to health and sustainability outcomes. For 13 cities across 10 middle- to high-income countries, we identified LPUGS ≥ 1 ha by fusing OpenStreetMap and satellite-derived Normalized Difference Vegetation Index data, and estimated residents' access within 500 m pedestrian network distance. We conducted a two-step validation process with local collaborators in each city. Our indicator methods identified LPUGS with greater than 80% accuracy for 12 of the 13 cities, and comparisons against official local reference data for four cities further demonstrated validity. While some open data limitations were identified, the indicators address critical gaps in existing methods by enabling standardized and comparable measurement of LPUGS in diverse cities internationally. Our customizable open-source global indicator tools can inform evidence-based green space planning for urban health and sustainability.
Keywords: 4406 Human Geography; 44 Human Society; Health Disparities; Behavioral and Social Science; Social Determinants of Health; Clinical Research; Generic health relevance; 11 Sustainable Cities and Communities; 3 Good Health and Well Being; 0406 Physical Geography and Environmental Geoscience; 0909 Geomatic Engineering; 1604 Human Geography; Geography; 3709 Physical geography and environmental geoscience; 4406 Human geography